Rol mediador de la policía nacional de Colombia en el posconflicto: Un estudio del discurso de expertos con AEDT (2016)
The results of this research are based on a theoretical review of recent national and international studies of the actions of security forces in post-conflict scenarios; in this study we also conducted a series of interviews with academics and experts in the Colombian political, economic and cultural fields. The product of these interviews was analysed using SATD (Statistical Analysis of Textual Data) with the SPAD software. With a quantitative and descriptive look, the use of this strategy helped generate knowledge about the “new roles” that must be assumed by the National Police of Colombia for the period after the Peace Accords, as a strategy for reconciliation of conflicting sectors and different social groups. Emerging dynamics of transformation or political, economic and socio-cultural changes are then made visible, that the national police must assimilate and implement in context.